Vitamin B12 effects on chlorinated methanes-degrading microcosms: Dual isotope and metabolically active microbial populations assessment - Rodriguez-Fernandez, Diana; Torrento Aguerri, Clara; Guivernau, Miriam; Vinas, Marc; Hunkeler, Daniel; Soler, Albert; Domenèch, Christina; Rosell, Mònica (My University, 2017)
Field-derived anoxic microcosms were used to characterize chloroform (CF) and carbon tetrachloride (CT) natural attenuation to compare it with biostimulation scenarios in which vitamin B12 was added (B12/pollutant ratio of 0.01 and 0.1) by means of by-products, carbon and chlorine compound-specific stable-isotope analysis, and the active microbial community through 16S rRNA MiSeq high-throughput sequencing. Autoclaved slurry controls discarded abiotic degradation processes. B12 catalyzed CF and CT biodegradation without the accumulation of dichloromethane, carbon disulphide, or CF. The carbon isotopic fractionation value of CF (ƐCCF) with B12 was −14 ± 4‰, and the value for chlorine (ƐClCF) was −2.4 ± 0.4‰. The carbon isotopic fractionation values of CT (ƐCCT) were−16±6 with B12, and−13±2‰without B12; and the chlorine isotopic fractionation values of CT (ƐClCT)were−6±3and−4±2‰, respectively. Acidovorax, Ancylobacter, andPseudomonaswere themost metabolically active genera,whereas Dehalobacter and Desulfitobacteriumwere below0.1% of relative abundance. The dual C-Cl element isotope slope (Λ = Δδ13C/Δδ37Cl) for CF biodegradation (only detected with B12, 7 ± 1) was similar to that reported for CF reduction by Fe(0) (8 ± 2). Several reductive pathways might be competing in the tested CT scenarios, as evidenced by the lack of CF accumulation when B12 was added, which might be linked to a major activity of Pseudomonas stutzeri; by different chlorine apparent kinetic isotope effect values and Λ which was statistically different with and without B12 (5 ± 1 vs 6.1 ± 0.5), respectively. Thus, positive B12 effects such as CT and CF degradation catalyst were quantified for the first time in isotopic terms, and confirmedwith themajor activity of species potentially capable of their degradation.Moreover, the indirect benefits
Keywords: Carbon tetrachloride; Chloroform; CSIA; Carbon chlorine isotope plot; MiSeq high-throughput sequencing; Pseudomonas stutzeri